2005
DOI: 10.1073/pnas.0502854102
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer to human joints: Progress toward a gene therapy of arthritis

Abstract: This article describes the clinical application of gene therapy to a nonlethal disease, rheumatoid arthritis (RA). Intraarticular transfer of IL-1 receptor antagonist (IL-1Ra) cDNA reduces disease in animal models of RA. Whether this procedure is safe and feasible in humans was addressed in a phase I clinical study involving nine postmenopausal women with advanced RA who required unilateral sialastic implant arthroplasty of the 2nd-5th metacarpophalangeal (MCP) joints. Cultures of autologous synovial fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(120 citation statements)
references
References 28 publications
(22 reference statements)
5
112
0
3
Order By: Relevance
“…In a separate study using mice that constitutively express human TNF␣, treatment with TNF mAb prevented further cartilage damage in older mice and actually promoted cartilage repair in younger mice (7-8 weeks of age) (50). Clinical trials have also shown the promise of IL-1Ra gene therapy for the treatment of arthritis (51). In our study, we provide evidence that IL-1Ra and TNF mAb may have beneficial effects on the meniscus, specifically for integrative meniscal repair in an inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 56%
“…In a separate study using mice that constitutively express human TNF␣, treatment with TNF mAb prevented further cartilage damage in older mice and actually promoted cartilage repair in younger mice (7-8 weeks of age) (50). Clinical trials have also shown the promise of IL-1Ra gene therapy for the treatment of arthritis (51). In our study, we provide evidence that IL-1Ra and TNF mAb may have beneficial effects on the meniscus, specifically for integrative meniscal repair in an inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 56%
“…33 Following genetic labeling of chondrocytes with GFP using a retroviral vector, Mierisch et al 34 observed a reduction of GFP-labeled chondrocytes from 100% of the initial density to 15% by 4 weeks after implantation into rabbit osteochondral defects. In our study, residual GFP expression was seen through 2 months in monolayer culture and through the 21-day study period in three-dimensional pellet culture.…”
Section: Aav-transduced Human Cells Improve Cartilage Repairmentioning
confidence: 99%
“…The safety of intraarticular IL-1Ra delivery has also been demonstrated in human clinical trials using single injections of 150 mg (15). As an alternative to the high and frequent dosing required for intraarticular protein delivery, animal studies have investigated IL-1Ra gene delivery via injection of either gene (16) or transfected cells (17), and exploratory clinical trials of such gene therapy have been performed in RA patients (18) and in OA patients (19).…”
mentioning
confidence: 99%